Biochar and compost amendments alter the structure of the soil fungal network in a karst mountainous area. (21st February 2022) - Yan, Taotao; Xue, Jianhui; Zhou, Zhidong; Wu, Yongbo
Abstract: The karst ecosystem is prone to degradation and this accounts for a large proportion of land degradation in southwestern China. In order to improve the nutrient status and microbial community structure of karst soil, the amendment method of combining biochar, compost, and chemical fertilizer l was explored. With CK as the control, M as manure compost, B as wood biochar, and F as chemical fertilizer, field trials were set up with eight treatments. The results showed that the biochar treatments led to higher fungal diversity and soil nutrient content than no‐biochar treatments, and the compost treatments resulted in higher fungal diversity and soil nutrient content than no‐compost treatments. Cluster and linear discriminant analysis effect size (LEfSe) analyses indicated that the composition and structure of the fungal community varied under different treatments; both the compost fungal network and biochar fungal network were more complex than their respective control networks. Soil carbon and nutrient fractions had significant effects on soil fungal networks. In short, the addition of both biochar and manure compost enlarged the complexity of microbial‐related networks and enhanced the soil nutrient status, indicating that biochar‐based fertilizer was beneficial in karst‐degraded soil restoration.